Removal of Lead(II) and Chromium(III) from aqueous solution by using organic-functionalized MCM-41 / Hamizah Md Rasid … [et al.] - Md Rasid, Hamizah; Aziz, Nafisah; Abdul Ghani, Fazni Susila; Abdullah, Noraishah (Faculty of Applied Sciences, 2020)
Ordered mesoporous silica with hexagonal structure, MCM-41 was synthesized under basic media using Ludox as the silica source and cetyltrimethylammonium bromide as the organic surfactant template. Organic-functionalized MPTS-MCM-41 were prepared by grafting method using 3- mercaptopropyltrimethoxysilane. The samples were characterized using FTIR, FESEM and XRD to obtain more detailed structural insights of MCM-41. The synthesized MPTS-MCM-41 were tested for adsorption of Pb(II) and Cr(III) ions in aqueous solution. Adsorption studies were analyzed using atomic absorption spectroscopy (AAS). The effect of adsorbent dose and contact time on the adsorption of Pb(II) and Cr(III) ions from aqueous solution have been investigated. MPTS-MCM-41 was found to be effective adsorbent for metal cation than parent MCM-41 with higher affinity for Pb(II) than Cr(III) from single solution. The highest percentage removal of Pb(II) was achieved at 94.59% using 0.4 g MPTS-MCM-41 at 4 hours contact time whereby the highest percentage removal of Cr(III) ions was achieved at 66.02% using 0.4 g MPTS-MCM-41 at 5 hours contact time.